EFFECT OF ASCORBIC ACID AND CALCIUM FOLIAR APPLICATION ON GROWTH, YIELD AND MARKETABILITY OF BROCCOLI - S. M. Ali,; B. H. Majeed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The experiments were carried out at the College of Agricultural Engineering Sciences - University of Baghdad during the fall season of 2021-2020 to study the effect of foliar application of ascorbic acid (0, 25, 50, 75 mg. L-1) which were symbolized as A0, A1, A2, and A3, and chelated calcium (0, 1.0, 1.5, 2.0 g. L-1) which were symbolized as Ca0, Ca1, Ca2, and Ca3 on the growth, yield and marketability of broccoli. A factorial experiment was carried out within the RCBD design, in a total of 16 treatments with three replicates. The main flowering heads were kept at temperatures 6-8° C for 20 days and 18-25° C for 4 days. The results were revealed that the individual and interaction treatments were recorded a significant values among the studied parameters, and the interaction treatment of A3Ca3  achieved the most significant increment of leaves area, total yield, heads weight, heads diameter, calcium content in leaves and heads, the chlorophyll and vitamin C content in the heads, 1962.54dm2.plant-1, 55.10 ton.ha-1, 889.78 g.head-1, 21.84 cm, 1.85% in leave, 1.68%, 152.35 mg.100g-1 and 305.07 mg.100g-1 respectively  decreased weight loss, increased total soluble solids, and maintained chlorophyll and vitamin C in the flowering heads after storage reached 11.40%, 134.72 and 96.41 mg.100g-1, 136.40 and 130.53 mg.100g-1 respectively at two temperatures.